Work Readiness of New Graduate Physical Therapists for Private Practice in Australia: Academic Faculty, Employer, and Graduate Perspectives - Wells, C.; Olson, R.; Bialocerkowski, A.; Carroll, Sara; Chipchase, L.; Reubenson, Alan; Scarvell, J.M.; Kent, F. (2021)
OBJECTIVE: The purpose of this study is to explore academic faculty, employer, and recent graduate perspectives of the work readiness of Australian new graduate physical therapists for private practice and factors that influence new graduate preparation and transition to private practice.